2014
DOI: 10.15560/10.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Large and medium-sized mammals of Carajás National Forest, Pará state, Brazil

Abstract: The Carajás National Forest is located in the Amazonian region, Pará State, Brazil and is part of a mosaic of conservation units comprising over one million hectares. This region has been explored for its mineral reserves, but knowledge of the distribution of animals and plants is lacking. The objective of this paper is to provide a list of the medium and large-sized mammals recorded from the Carajás NF. We used four methods to record mammals: linear transects, camera traps, records of road-killed animals, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…In Brazil, the giant armadillo lives in a variety of biomes which include the Amazon, the Atlantic Forest, the Cerrado and the Pantanal (Carvalho et al, 2014; Desbiez & Kluyber, 2013; Porfirio et al, 2012; Silveira et al, 2009; Srbek‐Araujo, Scoss, Hirsch, & Chiarello, 2009). On the Official List of Brazilian Fauna, it is also listed as Vulnerable to extinction (Instituto Chico Mendes de Conservação da Biodiversidade, 2018).…”
Section: Figurementioning
confidence: 99%
“…In Brazil, the giant armadillo lives in a variety of biomes which include the Amazon, the Atlantic Forest, the Cerrado and the Pantanal (Carvalho et al, 2014; Desbiez & Kluyber, 2013; Porfirio et al, 2012; Silveira et al, 2009; Srbek‐Araujo, Scoss, Hirsch, & Chiarello, 2009). On the Official List of Brazilian Fauna, it is also listed as Vulnerable to extinction (Instituto Chico Mendes de Conservação da Biodiversidade, 2018).…”
Section: Figurementioning
confidence: 99%
“…In this study Carnivora was the most speciose order, followed by Artiodactyla, in both PAs and IAs, suggesting that the structure of the mammalian community is preserved, although some of the species are generalist and matrix/fragmented tolerant species, such as Eira barbara. Studies in the Neotropics have shown that Carnivora is the most speciose order of large terrestrial mammals in protected areas, followed by Artiodactyla (Tobler et al 2008, Munari et al 2011, Springer et al 2012, Santos and Oliveira 2012, Ahumada et al 2013, Burton et al 2015, Michalski et al 2015, whereas in protected areas that are surrounded by human disturbances, Carnivora was followed by Rodentia and Xenarthra, which could represent an intermediate conservation status (Pickles et al 2011, Carvalho et al 2014, Lizcano et al 2016, or Rodentia could even be the most speciose order (Michalski et al 2015). In impacted areas, however, the most speciose order seems to be Xenarthra, followed by Rodentia Peres 2007, Botelho et al 2012).…”
Section: Determinants Of the Structure Of The Mammalian Assemblagesmentioning
confidence: 99%
“…Richness and diversity of terrestrial large mammals in the Neotropics is higher in strictly protected areas that are surrounded by other undisturbed forests than in those subject to deforestation and hunting in its surroundings, and is lowest in highly impacted areas (Tobler et al 2008, Ahumada et al 2011, Pickles et al 2011, Botelho et al 2012, Santos and Oliveira 2012, Carvalho et al 2014, Melo et al 2015, Meyer et al 2015. In strictly protected areas that are surrounded by other undisturbed forests, Carnivora and Artiodactyla are among the richest mammalian orders Oliveira 2012, Carvalho et al 2014), whereas in protected areas that are subjected to anthropogenic impacts in its surroundings, although Carnivora may still be the most speciose order, Rodentia and Xenarthra may replace Artiodactyla and become the most species-rich orders (Ahumada et al 2013, Michalski et al 2015, Lizcano et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we used the species A. belzebul , endemic to Brazil and occurring in a mixture of habitats, including the Amazon rainforest and fragments of the Brazilian Atlantic Forest, in the region of Veracruz, Mexico to Corrientes, Argentina (Nascimento, Bonvicino, de Oliveira, Schneider, & Seuánez, 2008). According to the classification of the Red List of Endangered Brazilian Fauna updated in 2018, the species A. belzebul is categorised as vulnerable and despite being ecologically flexible primates due to their geographical distribution and the diversity of habitats, primates of this species face serious extinction threats throughout its distribution (Carvalho et al., 2014; Fialho, Valença‐Montenegro, Silva, Ferreira, & Laroque, 2014).…”
Section: Introductionmentioning
confidence: 99%